Legal Consequences Of Typographical Errors In Notarial Minutes - Tarisya Eka Damayanti; Anang Shopan Tornado (JURNAL HUKUM SEHASEN, 2024)
The purpose of this research is as follows: To analyze the legal consequences for a notary's negligence in correcting typographical errors in notarial minutes, and to analyze the procedures followed by notaries in practice when typographical errors occur in notarial minutes. Legal research is divided into two types: Normative Legal Research and Empirical Legal Research. This study utilizes normative juridical research, analyzing legal regulations as its basis. Based on the types of data used, legal materials are categorized into primary legal materials, secondary legal materials, and tertiary legal materials. The research finds that a notary who neglects to correct typographical errors in notarial minutes may face civil and administrative sanctions. Typographical errors due to a notary's negligence can lead to civil lawsuits to claim compensation under Article 1365 of the Civil Code, as well as administrative sanctions under Article 85 of Law Number 2 Year 2014 concerning Notarial Office. Procedures for correcting typographical errors in notarial minutes include renvooi, corrections, or correction statements. Changes before the document is signed are termed renvooi and must be initialed by relevant parties, while changes after signing must be documented in a correction statement in the presence of the concerned parties and noted on the original notarial minutes. Copies of the correction statement must be provided to all parties involved. Failure by the notary to adhere to renvooi or correction procedures results in the document having evidentiary value as a private document only, and aggrieved parties may seek compensation from the notary.